Difference in Effectiveness between Progressive Muscle Relaxation and Butterfly Hug on Anxiety in the Elderly - Widyastuti, Arum; Erawati, Erna; Sugiarto, Angga; Suharsono, Suharsono (Muhammadiyah Journal of Geriatric, 2024)
Background: The Elderly, as a final stage in the development of human life, will face various health problems. Some physical and psychological body functions will decline. Mental health problems that are often experienced by the elderly include anxiety. Elderly people with anxiety symptoms require special attention through handling these symptoms. If not, these symptoms can harm the psychosocial condition of the elderly. Non-pharmacological treatments that are used as alternatives to overcome anxiety such as progressive muscle relaxation and the butterfly hug. Purposes: This study aims to analyze the difference in effectiveness of progressive muscle relaxation and the butterfly hug on elderly anxiety. Methods: This research design is quantitative with a quasi-experimental approach. The sampling technique was purposive sampling, and a total of 66 respondents were selected according to the predetermined restriction criteria and divided into two intervention groups. Data normality test using the Shapiro-Wilk, hypothesis testing using the Wilcoxon, and then a different test using the Mann-Whitney. Result: The results of data analysis of respondent characteristics showed the dominance of age in both intervention groups, namely, age 60-74 years. In the progressive muscle relaxation group, as many as 26 elderly people (78.8%), and in the butterfly hug group, as many as 19 elderly people (57.6%). Female gender (100%). The statement of the Wilcoxon test in each group indicated that the significance value was 0.001 (p)=0.001 0.005. Conclusion: This study shows the results that there is no significant distinction between progressive muscle relaxation and the butterfly hug on anxiety in the elderly.